Cutaneous Manifestations of Systemic Lupus Erythematosus. (7th June 2012) - Uva, Luís; Miguel, Diana; Pinheiro, Catarina; Freitas, João Pedro; Marques Gomes, Manuel; Filipe, Paulo
Abstract : Systemic lupus erythematosus (SLE) is a multiorgan autoimmune disease of unknown etiology with many clinical manifestations. The skin is one of the target organs most variably affected by the disease. The American College of Rheumatology (ACR) established 11 criteria as a classificatory instrument to operationalise the definition of SLE in clinical trials. They were not intended to be used to diagnose individuals and do not do well in that capacity. Cutaneous lesions account for four of these 11 revised criteria of SLE. Skin lesions in patients with lupus may be specific or nonspecific. This paper covers the SLE-specific cutaneous changes: malar rash, discoid rash, photosensitivity, and oral mucosal lesions as well as SLE nonspecific skin manifestations, their pathophysiology, and management. A deeper thorough understanding of the cutaneous manifestations of SLE is essential for diagnosis, prognosis, and efficient management. Thus, dermatologists should cooperate with other specialties to provide optimal care of SLE patient.